2022
DOI: 10.1002/ijc.33937
|View full text |Cite
|
Sign up to set email alerts
|

The association between bromodomain proteins and cancer stemness in different solid tumor types

Abstract: Cancer stemness, which covers the stem cell-like molecular traits of cancer cells, is essential for tumor development, progression and relapse. Both transcriptional and epigenetic aberrations are essentially connected with cancer stemness. The engagement of bromodomain (BrD) proteins-a family of epigenetic factors-has been presented in the pathogenesis of several tumor types, although their association with cancer stemness remains largely unknown. Here, we harnessed TCGA and GEO databases and used several bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…Furthermore, Patrycja et al. found a significant correlation between distinct BRDs and stemness maintenance in 27 solid cancer types ( 81 ). Hao and his colleagues found that EP300 could induce an increase in ALKBH5 expression to reduce the m6A level of FOXM1 mRNA by upregulating H3K27ac, resulting in enhanced FOXM1 mRNA levels and EMT cascade activation in melanoma ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Patrycja et al. found a significant correlation between distinct BRDs and stemness maintenance in 27 solid cancer types ( 81 ). Hao and his colleagues found that EP300 could induce an increase in ALKBH5 expression to reduce the m6A level of FOXM1 mRNA by upregulating H3K27ac, resulting in enhanced FOXM1 mRNA levels and EMT cascade activation in melanoma ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in pancreatic cancer, the upregulation of SMARCA2 associates with disease progression, being significantly positively correlated with patients’ poor survival, larger tumor size, metastases, lymphatic invasion, and stage IV disease [ 131 ]. We have recently reported a consistent negative association of SMARCA2 expression with cancer de-differentiation status [ 118 ]. However, the molecular studies demonstrating the precise role of SMARCA2 in the regulation of cancer stemness across distinct types of solid tumors are insufficient to make an unequivocal decision on whether SMARCA2 is a negative cancer stemness regulator.…”
Section: Several Brd Family Members Play a Fundamental Role In Cancer...mentioning
confidence: 97%
“…Recently, we have demonstrated that SMARCA4 exhibit a consistent positive correlation with cancer stemness (assessed based on transcriptomic features of TCGA cancers). At the same time, SMARCA2—shows a negative association with tumor de-differentiation status, regardless of the tumor type [ 118 ]. Indeed, the fundamental role of SMARCA4 in the regulation of cancer stemness was previously reported by Yoshikawa et al [ 119 , 120 ] in colorectal cancers.…”
Section: Several Brd Family Members Play a Fundamental Role In Cancer...mentioning
confidence: 99%
See 2 more Smart Citations